KUALITAS LABA YANG DIHASILKAN OLEH PENGADOPSIAN INTERNATIONAL FINANCIAL REPORTING STANDARDS - Irene Natalia (Jurnal Akuntansi Kontemporer, 2013)
Information needs of major users and information's quality for supplying sufficient business information became the focus by the company. The purpose of this article is to explain that IFRS adopters can increase their earning quality. The company can preparing financial reporting based on financial accounting standards applicable in the country where the entity is domiciled. Quality information, especially the quality of earnings, is an important priority for the user. The users expect good earnings quality in reporting after the adoption of IFRS. However, earnings quality is either not generated automatically by the good accounting and financial reporting standards because there are influencer factors that affect the quality of earnings and/or quality characteristics of the adoption of IFRS is a factor which is owned by IFRS adopters, environmental factors and capital market during the economic cycle adoption period, company's incentive factors, institutional factors, political non-participation factor in the process of implementing accounting standards, cultural factors that exist within a country, and the audit committee factor. Comparability is one wcry of measuring the quality of earnings. By considering all the benefits and advantages of adopting, IFRS should be applied by all countries in the world, although may result in less earnings quality that caused by influencer factors and the possibility of earnings management by corporate management.